Degradation of Atrazine over a heterogeneous photo-fenton process with iron modified MCM-41 materials - Benzaquén, Tamara Belén (2017)
In this work, MCM-41 materials have been synthesized and modified with different metal loadings of iron by the wet impregnation method. The different meso-structures obtained were characterized by XRD, UVVIS-RD, ICP and TEM and their behaviors as heterogeneous catalysts in the photo-Fenton reaction were studied. Thus, ironcontaining mesostructured materials have been successfully tested for the heterogeneous photo-Fenton degradation of atrazine aqueous solutions using UV?vis irradiation at room temperature and close to neutral pH. In order to assess the effectiveness of the herbicide degradation in the heterogeneous photo-Fenton process, and to compare experimental results obtained, a study of the photonic efficiency is presented. The photonic efficiency of Atrazine degradation was evaluated considering different experimental conditions employed two factorial designs. The results showed that the iron modified MCM-41 with a nominal metal loading of 2.5 wt.% exhibited the highest activity. Consequently, the high performance of this material indicates that the heterogeneous via of the photo-Fenton process can also be efficiently employed for the treatment of simulated wastewater containing atrazine, thus presenting advantages unlike the homogeneous process.